2021
DOI: 10.3390/jcm10235600
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Body Mass Index with Surgical Time Is Mediated by Comorbidity in Patients Undergoing Total Hip Arthroplasty

Abstract: Overweight represents a major issue in contemporary orthopaedic practice. A higher body mass index (BMI) is associated with an increase of perioperative complications following several orthopaedic procedures, in particular total hip arthroplasty (THA). However, the influence of overweight on THA surgical time is controversial. In this study, we investigated the association between BMI and surgical time analyzing the role of patients’ comorbidities. We conducted a retrospective study on 748 patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Obese patients tended to have longer Total Operating Room Times (TORT) and Surgical Operating Room Times (SORT), with no decrease in surgical efficacy 25–27 . This finding has been particularly well documented and should be taken into consideration when scheduling breast procedures 28,29 . Increased operative time may be due to general factors such as positioning, induction, and intubation, or technical challenges during surgery, such as more tissue to dissect and suture.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Obese patients tended to have longer Total Operating Room Times (TORT) and Surgical Operating Room Times (SORT), with no decrease in surgical efficacy 25–27 . This finding has been particularly well documented and should be taken into consideration when scheduling breast procedures 28,29 . Increased operative time may be due to general factors such as positioning, induction, and intubation, or technical challenges during surgery, such as more tissue to dissect and suture.…”
Section: Discussionmentioning
confidence: 88%
“…[25][26][27] This finding has been particularly well documented and should be taken into consideration when scheduling breast procedures. 28,29 Increased operative time may be due to general factors such as positioning, induction, and intubation, or technical challenges during surgery, such as more tissue to dissect and suture. This has significant financial implications, as average operating costs have increased from $20/min in 1991 to $46/min in 2022.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency in the literature and the findings in our study seem to emphasize the use of DMC in the elderly population, also highlighting that revisions are much more common in this age group. Several studies showed that obesity could be related to increased peri operative complications [ 24 , 25 ] and risk of failure because of the mechanical stress applied on the implant surfaces [ 26 ]. Unexpectedly, our results did not show differences between groups, and this can be interpreted from the limited cohort of patients when divided for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have not demonstrated statistical perioperative complication rate differences in patients undergoing TKRs or THRs across BMI categories ( 25 ). One retrospective study showed that overweight patients undergoing primary THR have a higher risk of increased surgical time and intraoperative blood loss, particularly if they present with multiple comorbidities ( 26 ). A recent study showed that obesity could increase perioperative blood loss but did not increase transfusion risk for patients undergoing simultaneous bilateral THRs.…”
Section: Discussionmentioning
confidence: 99%